2015
DOI: 10.1001/jamapediatrics.2015.0465
|View full text |Cite|
|
Sign up to set email alerts
|

Suicide Trends Among Elementary School–Aged Children in the United States From 1993 to 2012

Abstract: IMPORTANCE Suicide is a leading cause of death among school-aged children younger than 12 years but little is known about the epidemiology of suicide in this age group. OBJECTIVE To describe trends in suicide among US children younger than 12 years by sociodemographic group and method of death. DESIGN, SETTING, AND PARTICIPANTS Period trend analysis of national mortality data on suicide in children aged 5 to 11 years in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
149
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 21 publications
12
149
1
2
Order By: Relevance
“…4 Also, research has shown that black youth are less likely to receive services for depression, suicidal ideation, and other mental health problems compared with non-black youth. 3 by guest on March 23, 2019 www.aappublications.org/news Downloaded from racial disparities in precipitating circumstances within age group were examined in the current study, few differences were found. Suicide by hanging/strangulation/suffocation was more common among black decedents in both age groups, and black early adolescents who died by suicide were less likely to experience boyfriend/girlfriend problems or leave a suicide note than non-black youth.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…4 Also, research has shown that black youth are less likely to receive services for depression, suicidal ideation, and other mental health problems compared with non-black youth. 3 by guest on March 23, 2019 www.aappublications.org/news Downloaded from racial disparities in precipitating circumstances within age group were examined in the current study, few differences were found. Suicide by hanging/strangulation/suffocation was more common among black decedents in both age groups, and black early adolescents who died by suicide were less likely to experience boyfriend/girlfriend problems or leave a suicide note than non-black youth.…”
Section: Discussionmentioning
confidence: 69%
“…2 While our understanding of suicide in children remains limited, a recent analysis of suicide trends in US children (ages 5-11 years between 1993-1997 and 2008-2012) found a significant increase in the suicide rate among black children and a significant decrease for white children. 3 Given consistent observations that suicide rates for adolescents and young adults are higher in white subjects than in black subjects, 1, 4 -8 this report of a higher rate of suicide in elementary schoolaged black children raises questions about whether there are important racial and developmental differences in the underpinnings of suicide between elementary school-aged children and older youth.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…In a culture that maintains a patriarchal ideology that devalues intimate friendship by assigning it a devalued and demeaned sex (female) and sexuality (gay), the boys revealed signs of "maturing" into men who are autonomous, emotionally stoic, and isolated. The ages from 16 to 19 were not only a period of disconnection for the boys in Way's studies, it is also a period in development in which the suicide rate for boys across the USA rises dramatically [Bridge et al, 2015]. Just as the boys during early and middle adolescence predicted, giving up their closest male friendships in the name of not wanting to appear gay (e.g., "no homo") or girly makes them go "wacko.…”
Section: Resistance and Accommodation In Friendshipsmentioning
confidence: 97%